An Appraisal of the Role and Achievements of the Asean Regional Forum, 1994-2007 (Journal of International Studies, 2020)
The ASEAN Regional Forum (ARF) was inaugurated on 25 July 1994 in Bangkok by ASEAN - 6 in response to the general feeling among the nations of the Asia-Pacific area that a multilateral security arrangement was timely for the region. It was the realization of the 1992 Singapore Declaration of the Fourth ASEAN Summit which had proclaimed its desire to intensify ASEAN's external dialogue in political and security matters as a means of building cooperative ties with states in the Asia-Pacific region. The first meeting was attended by 18 states as follows: The six ASEAN members consisting of Brunei Darussalam, Indonesia, Malaysia, Philippines, Singapore and Thailand; seven ASEAN's Dialogue Partners consisting of Australia, Canada, the European Union, Japan, New Zealand, Republic of Korea and the United States; two ASEAN's Consultative Partners comprising China and Russia; and three ASEAN's Observers, consisting of Laos, Papua New Guinea and Vietnam. Since its formation in 1994, the ARF has come a long way and now (2007) boasts of a membership of 27 members 2 However there is a great deal of criticism that the ARF is ineffective in organization - a "talk-shop" which has become practically irrelevant. In these circumstances an evaluation of its achievements would be most appropriate.